2017
DOI: 10.1111/cen.13479
|View full text |Cite
|
Sign up to set email alerts
|

Age‐stratified thresholds of anti‐Müllerian hormone improve prediction of polycystic ovary syndrome over a population‐based threshold

Abstract: In this issue, Quinn et al report their experience on the diagnostic value of the anti-Müllerian hormone (AMH) assay for the recognition of polycystic ovary syndrome (PCOS). This subject remains very much debated and, in particular, there is no consensus on a specific threshold discriminating PCOS from normal women. One of the reasons, but certainly not the only one, is the heterogeneity of the control groups between the various studies reported to date. In their work, Quinn et al have benefited from the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Previous studies have found different AMH cut-off values to diagnose PCOS. However, because of small sample sizes, inappropriate controls and heterogeneous AMH assays ( 15 ), the application of these cut-offs in the diagnosis of PCOS has been limited. This might be why the introduction of AMH into the diagnosis of PCOS is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found different AMH cut-off values to diagnose PCOS. However, because of small sample sizes, inappropriate controls and heterogeneous AMH assays ( 15 ), the application of these cut-offs in the diagnosis of PCOS has been limited. This might be why the introduction of AMH into the diagnosis of PCOS is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Although AMH might serve as a potential diagnostic marker for PCOS, it is not currently recommended as a single-test parameter for this by the International Evidence-based Guideline for the Assessment and Management of Polycystic Ovary Syndrome 2018 ( 16 ). Comprehensive models have been established, combining AMH and other indicators ( 15 , 17 19 ). Vagios et al ( 18 ) have established a diagnostic model using AMH and BMI to predict PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we believe that a mathematical model combining AMH and age and other predictors, such as body mass index, might be required for the future diagnosis of PCOS. Age-stratified thresholds for AMH have been reported for the diagnosis of PCOS, 148 and AMH is predicted to replace AFC as a diagnostic indicator for this syndrome. 149 …”
Section: Amh and Pcos-like Phenotypesmentioning
confidence: 99%